2020
DOI: 10.1097/jcma.0000000000000461
|View full text |Cite
|
Sign up to set email alerts
|

Highlight of severe acute respiratory syndrome coronavirus-2 vaccine development against COVID-19 pandemic

Abstract: The pandemic caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) has brought an unprecedented impact upon the global economy and public health. Although the SARS-CoV-2 virology has been gradually investigated, measures to combat this new threat in public health are still absent. To date, no certificated drug or vaccine has been developed for the treatment or prevention of coronavirus disease Extensive researches and international coordination has been conducted to rapidly develop novel vacci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 49 publications
0
1
0
Order By: Relevance
“…Hence, further in vivo studies to validate our SP-based model are necessary, and future tests of um-PEA on human macrophages will be required. In conclusion, alongside a search for increasingly effective vaccines against variants of the SARS-CoV-2 virus [ 43 , 44 ], it is mandatory to identify and test molecules that can be therapeutically valid to prevent clinical worsening in the most severe cases of COVID-19. Considering that the protective effects of um-PEA in COVID-19 clinical management are the current objectives of two clinical trials (NCT04619706; NCT04568876), in the present work, we demonstrated a novel mechanism of action for um-PEA reinforcing the notion that this compound might significantly impact COVID-19 course.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, further in vivo studies to validate our SP-based model are necessary, and future tests of um-PEA on human macrophages will be required. In conclusion, alongside a search for increasingly effective vaccines against variants of the SARS-CoV-2 virus [ 43 , 44 ], it is mandatory to identify and test molecules that can be therapeutically valid to prevent clinical worsening in the most severe cases of COVID-19. Considering that the protective effects of um-PEA in COVID-19 clinical management are the current objectives of two clinical trials (NCT04619706; NCT04568876), in the present work, we demonstrated a novel mechanism of action for um-PEA reinforcing the notion that this compound might significantly impact COVID-19 course.…”
Section: Discussionmentioning
confidence: 99%
“…Ela alimenta o crescimento organizacional, impulsiona o sucesso futuro e é o motor que permite as empresas sustentarem sua viabilidade em uma economia global (GAYNOR, 2002). Para as empresas que buscam a excelência na era da hipercompetição, reduzir os custos e melhorar a qualidade do produto ou serviço não é mais o suficiente (LIN;CHEN, 2007).…”
Section: Referencial Teórico E Elaboração Do Modelo De Análiseunclassified
“…Enquanto algumas têm alcançado sucesso local, nacional e até mesmo internacional, inclusive ganhando prêmios importantes que promovem a marca e corroboram a qualidade de seus produtos, outras não conseguem a mesma performance (VASCONCELOS, 2017). A literatura sugere que o desempenho de uma empresa, em geral, poderia estar associado à sua capacidade de inovação (KNOWLES;HANSEN;SHOOK 2008;LEE;LEE;GARRETT, 2019;LIN;PENG;KAO, 2008;GUNDAY et al, 2011;RUBERA;KIRCA, 2012;VEIT, 2014). No segmento específico de micro e pequenas empresas, mais próximo do universo aqui de interesse, também é possível encontrar literatura que busca associar inovação com desempenho (ACS; AUDRETSCH, 1990;LIN;CHEN, 2007;ROSLI;SIDEK, 2013).…”
Section: Introductionunclassified
See 2 more Smart Citations